Elemental and radionuclide exposures and uptakes by small rodents, invertebrates, and vegetation at active and post-production uranium mines in the Grand Canyon watershed. (January 2021) - Cleveland, Danielle; Hinck, Jo Ellen; Lankton, Julia S.
Abstract: The effects of breccia pipe uranium mining in the Grand Canyon watershed (Arizona) on ecological and cultural resources are largely unknown. We characterized the exposure of biota to uranium and co-occurring ore body elements during active ore production and at a site where ore production had recently concluded. Our results indicate that biota have taken up uranium and other elements (e.g., arsenic, cadmium, copper, molybdenum, uranium) from exposure to ore and surficial contamination, like blowing dust. Results indicate the potential for prolonged exposure to elements and radionuclides upon conclusion of active ore production. Mean radium-226 in deer mice was up to 4 times greater than uranium-234 and uranium-238 in those same samples; this may indicate a potential for, but does not necessarily imply, radium-226 toxicity. Soil screening benchmarks for uranium and molybdenum and other toxicity thresholds for arsenic, copper, selenium, uranium (e.g., growth effects) were exceeded in vegetation, invertebrates, and rodents ( Peromyscus spp., Thomomys bottae, Tamias dorsalis, Dipodomys deserti ). However, the prevalence and severity of microscopic lesions in rodent tissues (as direct evidence of biological effects of uptake and exposure) could not be definitively linked to mining. Our data indicate that land managers might consider factors like species, seasonal changes in environmental concentrations, and bioavailability, when determining mine permitting and remediation in the Grand Canyon watershed. Ultimately, our results will be useful for site-specific ecological risk analysis and can support future decisions regarding the mineral extraction withdrawal in the Grand Canyon watershed and elsewhere. Highlights: First report of elements, radionuclides in biota at active, post-production uranium mines near Grand Canyon. Biota take up mining-related radionuclides, uranium, other elements. Some element concentrations remain elevated after cessation of active mining. Uranium, copper, arsenic, molybdenum, nickel, and lead may serve as mining signatures in biota. Prevalence and severity of lesions in livers and kidneys not definitively linked to mining.